Evaluation of satisfaction of students of doctor of physical therapy regarding their field of education - Qureshi, Bakhtawar Wajeeha; Qureshi, Muhammad Salman Haider (International Journal of Endorsing Health Science Research, 2013)
To assess the satisfaction level of students of Doctor of Physical Therapy (DPT) regarding their field of education. To identify the causes responsible for dissatisfaction of students with their field of study. Physical Therapy is an emerging and growing field in Pakistan and currently is passing through its stage of infancy. Five year program of Doctor of Physical Therapy (DPT) has been now introduced resulting in increased influx of students. Yet unawareness among the students as well as society still prevailed that resulted in confusing the minds of young undergraduate students of Physical Therapy. A cross-sectional study was conducted in the Institute of Physical Medicine and Rehabilitation, Peshawar. Total 100 students of Doctor of Physical Therapy. Were interviewed through structurally designed questionnaires. Ethical consideration was taken into account. The response rate was 78%. 55.1% students were found satisfied with the field, 7.6% were dissatisfied while 37.1% were unable to analyze whether satisfied or dissatisfied majority being basic sciences students. Students highlighted certain factors as responsible for their dissatisfaction.Majority of the students satisfied from their field of education belonged to clinical sciences which indicate their well-aware attitude about the significance of this field. Moreover, the students held disrespectful attitude of society, Limited facilities and job opportunities and Incapable Physical Therapists imparting bad name to this profession responsible for their dissatisfaction.